A Novel Componentless Power Quality Improvement Technique for Renewable Energy Sources - Ruban, A.Albert Martin; Anandaraj, R.; Kannan, N. (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
The main aim in power distribution system is to provide uninterrupted flow of energy at smooth sinusoidal voltage at the contracted magnitude level and frequency. However in wind power generation have numerous non linear loads, which significantly affect the quality of the power supplies. As the power of the non linear loads, the purity of the waveform of supplies is lost. In this proposed work, multiple port choppers is used to handle power quality issues such as voltage sags, harmonic distortion, in addition to normal wind turbine supplying to the customer during normal operation. The wind generation with micro turbine provides the flexibility of operation to the customer. The micro turbine based DVR can recover voltage sags in the supply voltage during abnormal load. On the other hand, it will operate as a separate DG when the wind power supply fails to supply the desired power.